Hickman catheter-related bacteremia with Kluyvera cryocrescens: a case report - (:unkn) unknown (NATL INST INFECTIOUS DISEASES, 2008)
This report describes a 2-year-old child with neuroectodermal tumor presenting with febrile neutropenia. Blood cultures drawn from the peripheral vein and Hickman catheter revealed Kluyvera cryocrescens growth. The Hickman catheter was removed and the patient was successfully treated with cefepime and amikacin. Isolation of Kluyvera spp. from clinical specimens is rare. This saprophyte microorganism may cause serious central venous catheter infections, especially in immunosuppressed patients. Clinicians should be aware of its virulence and resistance to many antibiotics.
Keywords: INFECTIONS; SUSCEPTIBILITY; ASCORBATA; GENUS; NOV